Foundation Character Participant Educating in the Era of Disruption Intelligence Artificial - Alex Alex; Habibah Pidi Rohmatu; Susanto Susanto (Jaanur Elbarik Indonesia, 2025)
This study aims to conceptually examine the urgency of strengthening the foundations of student character in the era of artificial intelligence disruption. This study uses a qualitative approach with library research methods through critical analysis of scientific literature, educational policies, and technology ethics studies. The results show that student character formation in the AI era must be based on fundamental values such as moral responsibility, integrity, critical digital literacy, empathy, and ethical awareness in the use of technology. Character education cannot be positioned as a complementary element, but rather as a primary foundation that must be integrated into the curriculum, school culture, and technology-based learning practices.